2001
DOI: 10.1163/15685680152692015
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing visual performance fields: effects of transient covert attention, spatial frequency, eccentricity, task and set size

Abstract: We investigated whether transient covert attention would differentially affect 'performance fields' (shape depicted by percent correct performance at particular locations in the visual field) for orientation discrimination, detection and localization tasks, while manipulating a number of visual factors. We found that although attention improved overall performance, it did not affect performance fields. Two patterns were observed regardless of the presence of a local post -mask, the stimulus orientation, or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

64
285
7
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(382 citation statements)
references
References 38 publications
64
285
7
3
Order By: Relevance
“…This effect was observed in both hemifields. This type of visual field asymmetry has been reported previously (19)(20)(21)(22). As a result, two probe locations, even adjacent, might present different report probabilities (i.e., P1 > P2) due to a position bias, rather than the kind of attentional effect under investigation here (one might speculate as to whether the position bias is, in turn, due to an attentional effect or some other spatially variable aspect of visual processing, but this question is beyond the scope of this investigation).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This effect was observed in both hemifields. This type of visual field asymmetry has been reported previously (19)(20)(21)(22). As a result, two probe locations, even adjacent, might present different report probabilities (i.e., P1 > P2) due to a position bias, rather than the kind of attentional effect under investigation here (one might speculate as to whether the position bias is, in turn, due to an attentional effect or some other spatially variable aspect of visual processing, but this question is beyond the scope of this investigation).…”
Section: Resultssupporting
confidence: 83%
“…A study in the macaque monkey showed that neurons in the frontal eye field respond sequentially to the items of a difficult search task, at a frequency of [18][19][20][21][22][23][24][25]. This finding was the first strong evidence of a link between attentional periodicity and sequential processing in visual search.…”
Section: Discussionmentioning
confidence: 91%
“…This lower intensity might be simply explained by the distance from the source to the electrodes, which would be shorter for area V3 compared to VP. However, some evidence suggests a real advantage for the lower hemifield, both in the strength of electrophysiological (Portin et al, 1999) and behavioral (Carrasco et al, 2001;Levine and McAnany, 2005;Liu et al, 2006) responses. This functional benefit might be explained by the anatomical overrepresentation of the lower hemifield in the retina (Perry and Cowey, 1985), the lateral geniculate nucleus (Connolly and Van Essen, 1984) and V1 .…”
Section: P1-n1 Complexmentioning
confidence: 99%
“…Using an orientation-defined target we recently encountered evidence seemingly at odds with both Korte's and Kooi and colleagues' ideas (Solomon, Felisberti & Morgan, 2004). In this now-popular paradigm (Baldassi & Burr, 2000, Cameron, Tai, Eckstein & Carrasco, 2004, Carrasco, Talgar & Cameron, 2001, Felisberti & Morgan, 2001, Morgan, Ward & Castet, 1998 observers must identify the orientation (as clockwise or anticlockwise of some reference orientation, usually vertical or horizontal) of a parafoveally presented Gabor target, when flanked by iso-eccentric Gabor distractors. We found that orientation identification was most difficult when distractor and target orientations differed by 22.5 -45 degrees (Solomon et al, 2004), contrary to the expectation that target salience would counteract crowding.…”
Section: Introductionmentioning
confidence: 99%